Integrated Diabetes Care : A Multidisciplinary Approach - Simmons, David; Wenzel, Helmut; Zgibor, Janice C. (Springer International Publishing : Imprint: Springer, 2017)
This book collates evidence of worldwide approaches to both horizontal integration (across disciplines) and vertical integration (across organizations) in diabetes care and describe what was done, what worked and what appeared to be the barriers to achieving the goals of the programmes. Evidence is sought from groups who have developed different approaches to integrating diabetes care in different health systems (such as insurance vs taxpayer funded, single vs multiple organization, published vs unpublished). A final chapter brings the evidence together for a final discussion about what seems to work and what does not. Integrated Diabetes Care - A Multidisciplinary Approach showcases innovative approaches to diabetes, showing the reader new ways by which problems are addressed and their putative outcomes.- Resumé vydavatel